Is COP30 a Step Forward from COP29? A Comparative Analysis of Climate Diplomacy and the Economic Consequences of Climate Change. - Mahmudova, Zahra; Hajiyeva, Nigar; Hajiyeva, Gunel (My University, 2026)
This paper aims to compare and contrast COP29 and COP30 through the lens of mitigation ambition, adaptation policies, and climate finance. Evaluating each annual COP as isolated annual events fails to capture the true trajectory of international climate negotiations. This study argues that COP is a continuous, evolutionary process, analyzing the evolution of global climate diplomacy since its beginning up until the transition from COP29 in Baku to COP30 in Belém. While individual summits are frequently criticized for incrementalism, tracing their historical progress reveals how foundational frameworks slowly transform into mandatory accountability mechanisms. COP29 focused heavily on expanding the global financial architecture through the New Collective Quantified Goal (NCQG) and finalizing Article 6 carbon market rules. COP30 served as the enforcement COP where nations had to submit revised, third- generation Nationally Determined Contributions (NDCs). By examining mitigation, adaptation, and financing across both summits, this study demonstrates that COP29 laid the financial groundwork, while COP30 tested the political will to execute those pledges. Ultimately, assessing these summits through a longitudinal lens proves that the COP process operates as a cumulative ratchet mechanism, where the pledges of one year dictate the compliance, transparency, and systemic progress of the next.
Keywords: UNFCCC; Climate diplomacy; Climate finance; Climate change mitigation; Climate change adaptation; Comparative policy analysis